The Effect of Project-Based Learning (PBL) on the Ability to Write Argumentative Texts in Grade XI Students at SMK Koperasi Pontianak - Arni, Arni; Fitriani, Fitriani; Reyzta, Reyzta (JURNAL RISET PENDIDIKAN DAN PENGAJARAN, 2025)
The ability to write argumentative texts is one of the important competencies that students must master in learning the Indonesian language. Through this skill, students are expected to be able to convey opinions, compose logical arguments, and develop a critical attitude towards various social phenomena in their surroundings. Even so, many students still experience difficulties in organizing coherent writing structures, selecting appropriate supporting data, and concluding ideas convincingly. This situation demands innovative learning models that can develop students' critical thinking skills as well as collaborative skills. The purpose of this study is to analyze the effect of implementing the Project Based Learning model on the ability to write argumentative texts of eleventh grade students at Koperasi Pontianak Vocational School. The method used is an experiment with a One Group Pretest-Posttest design. The research sample consists of 28 students selected through simple random sampling technique. The instrument is in the form of argumentative text writing tests given before and after the treatment. The results of the study show an increase in the average score from 53.11 (poor category) in the pretest to 83.57 (good category) in the posttest, with an increase difference of 30.46 points. Thus, PjBL model not only improves learning outcomes quantitatively, but also has a positive impact on students' engagement in the learning process. As such, students become more active in discussions, more critical in organizing arguments, and more skilled in developing logical and convincing written ideas.